Corporate social responsibility effect on firm's financial performance in Jordan. (24th August 2019) - Qaisi, Fouzan Al
The aim of the study investigates the impact of dimensions of corporate social responsibility (CSR) (environmental, community service, and human resources) on financial performance measured by return on assets (ROA). The sample of the study included the used (15) Jordanian companies listed in Amman stock exchange as a sample of this research during the period 2012-2016. To achieve the purposes of the study, and to analyse the data extracted from the annual reports, the researcher used simple and multiple linear regression methods. Social responsibility (environmental, community service, and human resources) on financial performance measured by ROA.